2022
DOI: 10.3390/su14042365
|View full text |Cite
|
Sign up to set email alerts
|

Train Operations Organization in High-Speed Railway Station Considering Variable Configuration

Abstract: The train operation problem at the railway station is one of the basic scheduling problems for railway companies, and the decomposition and combination of trains in station platform tracks is an important trend in the railway operation, which further increase the complexity of train routing problem in the high-speed railway station. A reasonable train routing plan is critical for ensuring the safety and efficiency of train operations within the stations. Considering the combination and decomposition process of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…Zhang et al [34] used the big-M method to minimize the train travel time and the maintenance tardiness; they added speed restriction constraints to the model. Xu et al [35] detailed the train formation process in high-speed railway stations and proposed a multiobjective programming model to minimize the train route cost and balance track allocation. Liao et al [36] integrated the TRP with the vehicle circulation problem, an integer programming model was proposed to maximize the overall transportation efficiency, and a Lagrangian relaxation algorithm was developed to solve the integrated model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zhang et al [34] used the big-M method to minimize the train travel time and the maintenance tardiness; they added speed restriction constraints to the model. Xu et al [35] detailed the train formation process in high-speed railway stations and proposed a multiobjective programming model to minimize the train route cost and balance track allocation. Liao et al [36] integrated the TRP with the vehicle circulation problem, an integer programming model was proposed to maximize the overall transportation efficiency, and a Lagrangian relaxation algorithm was developed to solve the integrated model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Liu et al developed an MINLP model to solve the real-time track reallocation problem [15]. Xu et al constructed a multi-objective model to determine the receiving routes and departure routes of trains [16].…”
Section: Literature Reviewmentioning
confidence: 99%
“…This aspect is critical for ensuring the safety of users, which number is increasing with an exponential law (Wijayanto, 2022). It is demonstrated that the decomposition processes of trains and stations can improve, for example, the occupancy balance of platform tracks and, consequently the safety of the total system (Xu, 2022). However, the consequence of an incident between a person and a train always has terrible consequences: suicide by train is a common case worldwide: victims place their bodies across the railroad tracks, leap in front of a moving train, or stand in front of it in order to be hit by it.…”
Section: Introductionmentioning
confidence: 99%